Predictors of remission in patients with non-radiographic axial spondyloarthritis receiving open-label adalimumab in the ABILITY-3 study - Robert Landewé; Xin Wang; Joachim Sieper; Marina Magrey; Jaclyn K Anderson; Sheng Zhong; Apinya Lertratanakul (RMD Open)
Background This analysis assessed baseline predictors of remission in patients with non-radiographic axial spondyloarthritis (nr-axSpA) who received open-label adalimumab therapy.Methods ABILITY-3 enrolled 673 adult patients with nr-axSpA who had objective evidence of inflammation by MRI or elevated high-sensitivity C reactive protein at screening, active disease and an inadequate response to two or more non-steroidal anti-inflammatory drugs. Patients received adalimumab 40 mg every other week during a 28-week open-label lead-in period. Clinical remission was defined as Ankylosing Spondylitis Disease Activity Score inactive disease (ASDAS ID; score <1.3) and Assessment of SpondyloArthritis international Society partial remission (ASAS PR; score <2/10 in each of the four ASAS domains). Stepwise logistic regression was used to identify baseline predictors of remission at week 12 and at final visit (last postbaseline visit up to week 28). Only patients without missing data were included.Results Overall, 593 patients were included in the ASDAS ID and 596 in the ASAS PR analysis at week 12. Younger age (≤45 years), male sex, positive human leucocyte antigen (HLA)-B27 and higher Spondyloarthritis Research Consortium of Canada (SPARCC) MRI sacroiliac joint score were consistent predictors of remission by both ASAS ID and ASDAS PR at week 12. Results were generally similar in the final visit analysis. Other variables did not consistently predict remission.Conclusions In ABILITY-3, consistent and strong baseline predictors of remission included younger age, male sex, HLA-B27 positivity and higher SPARCC MRI sacroiliac joint score among patients with active nr-axSpA receiving adalimumab therapy, similar to previous findings in ankylosing spondylitis.